Índices de qualidade biológica do solo em área sob manejo de adubos verdes - Sosa, Karla Selene Forstall (2019)
In the search for a sustainable agriculture the use of plant species that promotes soil biological properties has been considered as an alternative to soil conservation practices. Our aim here was to evaluate the effects of plant species cultivation on both the soil macroarthropods and arbuscular mycorrhizal fungi communities in a semiarid ecoregion. The study was developed in field conditions, using a randomized blocks design with ten treatments (Crotalaria juncea L., C. spectabilis Roth, C. ochroleuca G. Don, Canavalia ensiformis (L.) DC., Dolichos lablab L., Mucuna pruriens (L.) DC., Stilozobium aterrimum Piper & Tracy, Neonotonia wightii (Wight & Arn.) J.A. Lackey, Pennisetum glaucum (L.) R. Br., and a control treatment (a mix of Brachiaria decumbens Stapf cv. Basilisk and native weeds), in three independent blocks. In order to evaluate the effects of plant species cultivation on both the soil macroarthropod and arbuscular mycorrhizal fungal communities, we evaluated the plant dry biomass production, soil pH, soil total organic carbon, species richness (S), Shannon’s diversity index (H') and Simpson’s dominance index (C). For the effects of plant species cultivation on arbuscular mycorrhizal fungi (AMF) communities, we compared our results with two additional control treatments (Eucalyptus globulus Labill and a tropical moist forest). The Shapiro-Wilk test was applied to assess the normality of the data distribution. Two-way ANOVA was used to test significant differences between species richness, H’ index, and C index. The Bonferroni’s test was applied at 5% probability. Based on our results, we generated two equations to estimate the soil biological quality index (IQBS), as well as the mycorrhizal quality index (IQM). We found the highest values of soil macroarthropod richness and H’ index in the plots where C. spectabilis and C. ochroleuca were cultivated. The plant species with the best results in the ecological indexes were P. glaucum, C. ensiformis, S. aterrimum and N. wightii, when compared with Eucalyptus globulus Labill and tropical moist forest.